Study on Start-Ups in Romania - Cristina Elena Bigioi; Mirabela Andreea Budulan (Communications of International Proceedings, 2020)
Entrepreneurs are the ones who are the basis of the economy. Through their activity, they allow the development of transactions, create products and services, and offer them to consumers internationally. At the same time, the activity of the commercial companies ensures the incomes necessary for the functioning of the state. A challenge for entrepreneurs is to ensure the financing of the company's activity. The state offers the possibility to some companies to benefit in certain conditions from the necessary funds for carrying out the activity. The present study follows the evolution of some companies that benefited from such funds in the first edition of Start-Up Nation held in Romania. The study of the 25 companies shows that many entrepreneurs relied on this financing to run the business, and only a few understood that the success of the business does not consist only in this money (which are few anyway). These funds allowed the purchase of equipment, they were a plus, but the success of the company did not depend on them.
Keywords: Entrepreneurship; Performance; Evolution; Non-Reimbursable Funds